The narrative policy framework and institutions. - McGovern, Rachel; Jones, Michael D. (Review of Policy Research, 2025)
This paper re‐evaluates conventional Institutional Analysis and Development (IAD) scholarship which has traditionally prioritized the study of specific rules configurations and their role in forming effective institutional arrangements. We suggest that effective institutional governance may actually be more reliant on the narrative foundations and personal cognitive interpretations of these rules than on the explicit rules themselves. By drawing insights from the Narrative Policy Framework (NPF), which delves into the internal cognitive processes of individuals, we seek to enrich the understanding of institutional‐actor‐rule dynamics. We contend that policy actors often rely on narrative heuristics to navigate complex institutional landscapes, underscoring the role of narratives in both understanding institutional structures and instigating collective action. Although institutional scholarship recognizes the centrality of communication, its impact on shaping institutional arrangements and rule formation remains insufficiently explored. This paper advocates for the integration of the NPF and the Institutional Grammar Tools' (IGT) ADICO, identifying potential parallels between the two frameworks. Our preliminary theorization suggests a cyclical relationship between narratives and institutions, with narratives shaping and being shaped by institutional rules and norms. Building upon Narrative Attention Theory, we aim to understand the broader implications of institutional narratives in driving or reinforcing policy stasis. Our paper represents a foundational step toward a comprehensive theoretical framework on the role of narratives in institutions, spotlighting institutional rules and pointing to future research directions. Through the proposed integration of NPF and IGT's ADICO, we hope to provide a more nuanced understanding of narrative dynamics in institutional arrangements and pave the way for empirical exploration of this relationship.